Multi Sistem Pendidikan Pesantren dan Tantangan Masa Depan - Safradji Safradji (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
Pesantren or Pondok Pesantren are Islamic boarding school. According to onepopular tradition. As social institutions, pesantren have played a major role overthe centuries. They emphasise cores values of sincerity, simplicity, individualautonomy, solidarity and self-control. Young men and women are separated fromtheir familier, which contributes to a sense of individual commitment to the faithand close bonding to a teacher. Pesantren aim to deepen knowledge of Qur’an,particularly thruugh the study of Arabic, traditions of exegesis, the Sayings of theProphet, law and logic. The term pesantren derives from the root word santri orstudent – pe-santri- or the place of the santri. Pesantren provides to Indonesiancitizens at low cost; although today some modern pesantren charge higher feesthan previously, they are still significantly cheaper than non-pesantreneducational instittutions. The tradisional pattern was for students to work in theheadmaster’s rice fields in exchange for food, shelter, and education. Allpesantren are led by a group of teachers and religious leaders known Kyai. TheKyai is respected as teacher and devout man. Kyai also play important roles in inthe community as a religious leader and in recent years as a political figure.There are Kyai families that have a long history of serving in this role. Somecontemporary Kyai are the grandsons and great-grandsons of famous historialfigures who established well known pesantren